Strategi Bisnis Pendekatan Metode SWOT Pada Usaha Petani Tambak Udang Vannamei Tahun 2023 - Latifah Munawaroh; Suwarto; Fitriani (Jurnal Manajemen DIVERSIFIKASI, 2026)
Aquaculture has an important role in achieving prosperity in most Indonesian communities, especially for people who live in water areas, one of which is cultivating vannamei shrimp in Wachyuni ​​Mandira village. This research focuses on analyzing business strategy development using SWOT analysis (IFE, EFE, IE, SWOT Matrix, SWOT Quadrant, QSPM). The method used in this research is quantitative with a descriptive approach, data collection techniques through interviews, observation and documentation using a quota sampling technique to obtain a sample of 15 people. The results of the SWOT analysis show that the business is in quadrant 1, which means the business is making progress with good opportunities and strengths. The results of this research are that the IFE owned by this business has 8 factors consisting of 4 strength factors and 4 weakness factors. This business has 8 EFE factors consisting of 4 opportunity factors and 4 threat factors. For the IE matrix, it is in cell V position, namely the guarding and defending position. The venamei shrimp pond business in Wachyuni ​​Mandira village has 13 alternative strategies. The priority strategy for the venamei shrimp pond business in Wachyuni ​​Mandira village is taking sea water 50 m away with the aim of ensuring that the water is not contaminated with a score of 20.64.